A novel dimethyl sulfoxide/1, 3-dioxolane based electrolyte for lithium/carbon fluorides batteries with a high discharge voltage plateau. (20th August 2015) - Pang, Chengkai; Ding, Fei; Sun, Wenbin; Liu, Jiaquan; Hao, Mingming; Wang, Ying; Liu, Xingjiang; Xu, Qiang
Abstract: A novel dimethyl sulfoxide/1, 3-dioxolane (DMSO/1, 3-DO) based electrolyte is proposed for lithium/carbon fluorides (Li/CFx ) batteries to enhance the discharge voltage plateau and energy density. Conductivities of the electrolyte of 1 mol L −1 LiBF4 /DMSO+1, 3-DO with different volume ratios are not identical, which have a maximum of 14.85 mS cm −1 . From the tests of galvanostatic discharge, the discharge voltage plateau of the Li/CFx battery with an electrolyte of 1 mol L −1 LiBF4 /DMSO+1, 3-DO (5:5, v:v) can reach 2.69 V at 0.1 C, delivering a maximum discharge capacity of 831 mAh g −1 and the highest energy density of 2196 Wh kg −1 . Compared to Li/CFx batteries with an electrolyte of 1 mol L −1 LiBF4 /PC+DME (5:5, v:v), the energy density of Li/CFx batteries with an electrolyte of 1 mol L −1 LiBF4 /DMSO+1, 3-DO (5:5, v:v) has been improved more than 12%. With the help of XRD, SEM, TEM, EIS, FT-IR and GC-MS analysis, the results of this work suggest that DMSO/1, 3-DO based electrolyte can significantly improve the discharge performance of Li/CFx batteries and keep a good electrochemical stability during discharge. The main reason for improvement of discharge performance is decreasing of both the overpotential of electrochemical polarization of CFx cathodes during discharge and the overpotential of ohmic polarization by increasing the ion conductivity of electrolyte.